Metagenomic analysis of the rumen microbial community following inhibition of methane formation by a halogenated methane analog - Denman, Stuart E.; Martinez Fernandez, Gonzalo; Shinkai, Takumi; Mitsumori, Makoto; McSweeney, Christopher S. (Frontiers in Microbiology, 2015)
Japanese goats fed a diet of 50% Timothy grass and 50% concentrate with increasing levels of the anti-methanogenic compound, bromochloromethane (BCM) were investigated with respect to the microbial shifts in the rumen. Microbial ecology methods identified many species that exhibited positive and negative responses to the increasing levels of BCM. The methane-inhibited rumen appeared to adapt to the higher H2 levels by shifting fermentation to propionate which was mediated by an increase in the population of hydrogen-consuming Prevotella and Selenomonas spp. Metagenomic analysis of propionate production pathways was dominated by genomic content from these species. Reductive acetogenic marker gene libraries and metagenomics analysis indicate that reductive acetogenic species do not play a major role in the BCM treated rumen.